Identification and genotyping of Enterocytozoon bieneusi among human immunodeficiency virus infected patients - Sonali Khanduja; Ujjala Ghoshal; Vikas Agarwal; Priyannk Pant; Uday C. Ghoshal (Elsevier, 2017)
Summary: Microsporidia cause diarrhea among human immunodeficiency virus (HIV) infected patients worldwide. Enterocytozoon bieneusi and Encephalitozoon intestinalis are the most common species infecting HIV patients. Various genotypes of E. bieneusi are transmitted from human to human (anthroponotic route) or from animal to human (zoonotic route). However, there is no study from India on genotypes of E. bieneusi among infected hosts. Therefore, we aimed to (a) study the prevalence, clinical symptoms, and species identification of microsporidia among HIV infected patients and (b) perform a genotypic analysis of E. bieneusi and a phylogenetic interpretation of the transmission of different genotypes among infected hosts. Two hundred and twenty-two HIV-infected patients and 220 healthy controls (HC) were tested for the presence of microsporidia using modified trichrome (MT) staining and PCR. Demographic, clinical and laboratory parameters were studied. Species identification was performed using PCR-RFLP. All E. bieneusi isolates were subjected to genotypic and phylogenetic analysis. Patients with HIV [n = 222, age 37.4 ± 10.4 y, 169 (76%) male] were more commonly infected with microsporidia than the HC [n = 220, age 34.5 ± 6.5 y, 156 (71%) male], using MT stain and PCR [4/222, 1.8% vs. 0/220, p = 0.04]. Patients infected with microsporidia more commonly presented with diarrhea than those not infected with microsporidia [4, 100% vs. 98/218, 45%; p = 0.04]. E. bieneusi was detected in all patients with microsporidia. Four novel genotypes (Ind1 to Ind4) were identified. Ind1 showed 95% similarity with genotype L (AF267142.1) reported in cats (Germany). Genotypes Ind2 to Ind4 showed 94-96% similarity to host-specific genotype A (AF101197.1) reported in humans. Phylogenetic analysis mainly showed an anthroponotic route of transmission (3/4), while the zoonotic route (1/4) was also observed. The prevalence of microsporidia among HIV-infected patients was 1.8%. Patients with microsporidia commonly present with diarrhea. E. bieneusi is the most common species infecting the study population. Four novel genotypes of E. bieneusi were identified, suggesting presumptive transmission mainly through the anthropological route. Keywords: Microsporidia, Diarrhea, Internal transcribed spacer, Phylogenetic analysis